Estimating the population distribution of usual 24-hour sodium excretion from timed urine void specimens using a statistical approach accounting for correlated measurement errors. - Wang, Chia-Yih; Carriquiry, Alicia L; Chen, Te-Ching; Loria, Catherine M; Pfeiffer, Christine M; Liu, Kiang; Sempos, Christopher T; Perrine, Cria G; Cogswell, Mary E (Journal of Nutrition, 2015)
Background: High US sodium intake and national reduction efforts necessitate developing a feasible and valid monitoring method across the distribution of low-to-high sodium intake.Objective: We examined a statistical approach using timed urine voids to estimate the population distribution of usual 24-h sodium excretion.Methods: A sample of 407 adults, aged 18-39 y (54% female, 48% black), collected each void in a separate container for 24 h; 133 repeated the procedure 4-11 d later. Four timed voids (morning, afternoon, evening, overnight) were selected from each 24-h collection. We developed gender-specific equations to calibrate total sodium excreted in each of the one-void (e.g., morning) and combined two-void (e.g., morning + afternoon) urines to 24-h sodium excretion. The calibrated sodium excretions were used to estimate the population distribution of usual 24-h sodium excretion. Participants were then randomly assigned to modeling (n = 160) or validation (n = 247) groups to examine the bias in estimated population percentiles.Results: Median bias in predicting selected percentiles (5th, 25th, 50th, 75th, 95th) of usual 24-h sodium excretion with one-void urines ranged from -367 to 284 mg (-7.7 to 12.2% of the observed usual excretions) for men and -604 to 486 mg (-14.6 to 23.7%) for women, and with two-void urines from -338 to 263 mg (-6.9 to 10.4%) and -166 to 153 mg (-4.1 to 8.1%), respectively. Four of the 6 two-void urine combinations produced no significant bias in predicting selected percentiles.Conclusions: Our approach to estimate the population usual 24-h sodium excretion, which uses calibrated timed-void sodium to account for day-to-day variation and covariance between measurement errors, produced percentile estimates with relatively low biases across low-to-high sodium excretions. This may provide a low-burden, low-cost alternative to 24-h collections in monitoring population sodium intake among healthy young adults and merits further investigation in other population subgroups.